MASS PARTITION DURING COLLAPSING AND TRANSITIONAL COLUMNS BY USING NUMERICAL SIMULATIONS - Neri A.; Di Muro A.; Rosi M. (My University, 2002)
Pyroclast dispersal and mass partition between convective and collapsing transport systems represent a major issue in the understanding of the dynamics of quasi-steady explosive eruptions and the interpretation of their deposits. The spatial and temporal dispersal of pyroclasts during the initial 15 min of collapsing and transitional columns was investigated by using a transient, two-dimensional and three-phase (one gas phase and two solid phases representative of pyroclasts of varying size and density) flow model. The different behaviors of the column were simulated by using different water contents of the eruptive mixture and assuming both pressure-balanced and overpressured conditions at the vent. For each simulation results allowed the quantification of the mass of pyroclasts of different size forming the pyroclastic density current, the co-ignimbrite column and the convective plumes rising from the proximal area and above the fountain. For collapsing columns, the total mass transported in the convective system (composed of the plume above the fountain and the co-ignimbrite column) ranges from about 10 to 30 wt% of the total erupted mass according to the specific water content of the mixture at the vent. Fine particles are dominant in this convective system. With the increase of the water content the character of the column shows a collapsing/buoyant transitional behavior. Such a regime is characterized by greater collapse height, generation of more dilute density currents, shorter flow runout, less steady behavior of the column, and intermittent feeding of the flows. For these columns, the total mass forming the convective portions reaches values of up to 50 wt% of the erupted pyroclasts with a significant amount of coarse particles entrained in the convective plume above the fountain. At higher water contents the column becomes fully buoyant with the whole mass feeding the convective column. Simulations assuming overpressured conditions at the vent are characterized by more unsteady dynamics of the dispersal process with significant variations in the collapse height of the column, mass flow-rate of the flow and amount of mass elutriated in the convective system. Simulation results suggest that Plinian columns that undergo a transition from convective to collapsing regimes, as a consequence, in our case, of a water content decrease in the magma (but not necessarily limited to this case), would be characterized by a gradual decrease of the carrying capacity of the convective column above the fountain and by the emplacement of pyroclastic density currents which evolve from dilute to dense, gradually increasing their runout.
Keywords: MASS PARTITION; ERUPTION DYNAMICS; COLLAPSING COLUMNS; TRANSITIONAL COLUMNS; MULTIPHASE FLOW MODEL